Entrepreneurial Team Knowledge Diversity and Creativity: A Multilevel Analysis of Knowledge Sharing, Individual Creativity, and Team Creativity - Hou, Fei; Su, Yu; Qi, Mingde; Wang, Lihua; Wang, Qian (Frontiers in Psychology, 2021)
Although the academic community has consistent with the key role of entrepreneurial team knowledge diversity, which serves as a critical catalyst of creativity in organizations, the extant research on the link between knowledge diversity and creativity is mainly concerned with individual creativity in single-level analyses. With emerging entrepreneurial ventures increasingly relying on innovation enhancement in the form of teams, there is research motivation to explore how team-level creativity develops. In this sense, this study attempts to investigate the underlying mechanism through which entrepreneurial team knowledge diversity is associated with team-level creativity. Through a multilevel mediation model, this study proposes that entrepreneurial team knowledge diversity can facilitate team creativity sequentially transmitted through individual-level team members’ knowledge sharing and creativity. Based on a survey of 252 team members from 42 entrepreneurial teams in China, multilevel structural equation modeling (MSEM) is applied to test the top-down relationship between entrepreneurial team knowledge diversity and knowledge sharing, as well as the bottom-up link between individual creativity and team creativity. The findings show that our hypotheses are supported. Our findings provide some of the first empirical evidence to examine how knowledge-based diversity of entrepreneurial teams facilitates team creativity potential by multilevel approach. Theoretical contributions and practical implications are also offered.